Predicting of equation thermo-electric currents and cutting conditions generated in face milling - Kovač, Pavel; Milikić, Dragoje (Journal of Production Engineering, 1985)
This article deals with the determination of thermoelectric currents in face milling, describes the measuring equipment and computer use. Some results, including the variation of thermoelectric currents with cutting speed, feed rate, and depth of cut, are presented.